Using Multiple Questioning Strategies Viewed from Teachers’ and Students’ Perspectives - Supriusman, Supriusman; Yunus, Melor Md; Mohd Yasin, Mohd Hanafi (JR-ELT (Journal of Research in English Language Teaching), 2017)
The current study was carried out to identify teachers’ perspectives regarding their knowledge and comprehension towards questioning strategies and its implementation as well as the extent to which it effects towards students’ acceptance in improving their learning motivation, critical thinking skills and English proficiency. Meanwhile, from the students’ perspectives, the focus of the study was on the extent to which their acceptance towards their learning motivation, critical thinking skills and English proficiency. This survey utilised a set of questionnaires as the main instrument. A number of 160 English teachers and as 1600 secondary school students from Pekanbaru, Riau Indonesia involved in this study. They were recruited by using stratified random sampling. An overall pilot test result using Chronbach’s Aplha analysis revealed that there was a high reliability for all the constructs i.e. 0.772 to 0.962. Data analysis of the present study uses SPSS 22.0 involving descriptive analysis (mean and standard deviation) and inferential statistics involving MANOVA and regression. Overall results demonstrated that the teachers’ knowledge and comprehension regarding questioning strategies and its implementation were at the moderate levels. Meanwhile, differential analysis revealed that there was no significant difference between genders and teaching experience for some constructs. Regression analysis showed that questions’ preparation was a dominant contribution towards its implementation (55.5%). From the students’ perspectives, overall results revealed that students’ acceptance towards various questioning strategies were at the moderatelevels where some of them were at the higher level. Differential statistical analyses results showed that there were some differences between genders with regards to the questioning strategies implemented. Regression analysis demonstrated that types or formats of questions contributed 55.4% towards English proficiency among students. Implications of this study have highlighted using multiple questioning strategies can be used as an approach to overcome English language problems among students.